Ladlad 2 : An anthology of philippine gay writing - Garcia, J. Neil C;Remoto, Danton ([Place of publication not identifed] : [publisher not identified], 1996)
This book escapes the sexualizing imperative of which we speak because other than celebrate gayness as it is being lived by Filipinos who know they are gay because of the way they desire, it attempts to lay bare the areas of filipino life in which the homo/hetero distinction does not and cannot operate.
Essays -- Poems -- Stories.
Keywords: PHILIPPINE LITERATURE -- ENGLISH AND FILIPINO